Experimental Investigations of the Self-Controlled Synchronous Motor Connected to a Three-Phase Line Commutated SCR Inverter - Tapan Kumar Chakraborty (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper concerns the experimental investigations of the three-phase line commutated SCR inverter fed synchronous motor.  The fabricated system consists of a line-commuted inverter, a three-phase synchronous motor with the excitation winding connected in series to the inverter input, a terminal voltage sensor and a gate-pulse generating circuit. The firing pulses for SCRs of the inverter are generated by the microprocessor in proper sequence with the help of synchronizing signal derived from the terminal voltages of the synchronous machine. The steady state performance characteristics are obtained experimentally using the fabricated system. The experimental results show that a three-phase synchronous motor supplied by a line commutated inverter with the excitation winding connected in series to the dc link provide  excellent characteristics of the conventional dc series motor.